Ethylene Signaling Is Required for Fully Functional Tension Wood in Hybrid Aspen - Seyfferth, Carolin; Wessels, Bernard A.; Gorzsás, András; Love, Jonathan W.; Rüggeberg, Markus; Delhomme, Nicolas; Vain, Thomas; Antos, Kamil; Tuominen, Hannele; Sundberg, Björn; Felten, Judith (Frontiers in Plant Science, 2019)
Tension wood (TW) in hybrid aspen trees forms on the upper side of displaced stems to generate a strain that leads to uplifting of the stem. TW is characterized by increased cambial growth, reduced vessel frequency and diameter, and by the presence of gelatinous, cellulose-rich (G-)fibers with its microfibrils oriented parallel to the fiber cell axis. Knowledge remains limited about the molecular regulators required for the development of this special xylem tissue with its characteristic morphological, anatomical and chemical features. In this study we use transgenic, ethylene insensitive (ETI) hybrid aspen trees together with time-lapse imaging to show that functional ethylene signaling is required for full uplifting of inclined stems. X-ray diffraction and Raman microspectroscopy of TW in ETI trees indicate that, although G-fibers form, the cellulose microfibril angle in the G-fiber S-layer is decreased and the chemical composition of S- and G-layer is altered compared to wild type TW. The characteristic asymmetric growth and reduction of vessel density is suppressed during TW formation in ETI trees. A genome-wide transcriptome profiling reveals ethylene dependent genes in TW, related to cell-division, cell wall composition, vessel differentiation, microtubule orientation and hormone crosstalk. Our results demonstrate that ethylene regulates transcriptional responses related to the amount of G-fiber formation and their properties (chemistry and cellulose microfibril angle) during TW formation. The quantitative and qualitative changes in G-fibers are likely to contribute to uplifting of stems that are displaced from their original position.